Subsidized earmarked credit under incomplete markets - Costa, Pedro Henrique Zecchin (2024)
Government intervention in the credit market is common, especially in developing countries. One of such interventions is to subsidize credit to some firms. This policy is particularly present in the Brazilian credit market, where more than half of the outstanding credit was earmarked in 2016. To understand the effects of this policy, I build an incomplete markets model that includes subsidized earmarked credit and two types of agents - workers and capitalists. Calibrating the model for Brazil during a period of expansion of this policy, I show that in a counterfactual world without subsidies, the economy’s productivity would be higher, the steady-state interest rate would be substantially lower, and the welfare of workers, particularly the poor, would be higher. Nevertheless, I show that the optimal subsidy rate isn’t zero: a policy of moderate subsidy can improve welfare by partially offsetting the markets’ incompleteness.